Validation of the MORISE Learning Model on the Topic of Global Warming to Enhance Science Literacy and Learning Outcomes - Isna Nur Aisiyah; Joko Waluyo; Dwi Wahyuni (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
This study aims to examine the validity of the MORISE learning model. The research design used follows the Education Research and Development method, which involves the development of the model starting from designing the model to implementing it. The validity test of the MORISE model is conducted by two science education faculty members from the Postgraduate Program at UNEJ as expert validators, and one user validator, with the purpose of obtaining feedback and improvements for the learning model developed by the researcher. The first expert validator gave a score of 93%, the second expert validator gave a score of 84%, and the user validator gave a score of 95%. The average result of the final validation is 91%, falling within the highly valid criteria (>81.25%), thus indicating that the MORISE learning model can be used without revisions.